IMMUNOGLOBULIN GENE REARRANGEMENT IN DETECTION OF MINIMAL RESIDUAL DISEASE IN ACUTE LYMPHOBLASTIC LEUKAEMIA - Nayyar, Ayesha; Ahmed, Suhaib (Journal of Ayub Medical College Abbottabad, 2013)
Background: Acute lymphoblastic leukaemia (ALL) is mainly a childhood malignancy but affects both children and adults. Objective: The study was conducted to evaluate a qualitative PCR based method for detection of clonal immunoglobulin gene rearrangement as a marker of minimal residual disease in patients of acute lymphoblastic leukaemia at the end of induction. Method: It was a descriptive study conducted at Armed Forces Institute of Pathology, Rawalpindi from Aug 2009 to Feb 2010. For prospective analysis, genomic DNA was extracted from peripheral blood/bone marrow aspirates and unstained bone marrow smears. A total of 50 patients of acute lymphoblastic leukaemia who showed positive immunoglobulin gene rearrangement by qualitative PCR at the time of diagnosis were included. These patients were then investigated for minimal residual disease at the end of induction. PCR amplification of the IgH gene was done by a VH primer homologous with a highly conserved sequence near the 3´ end of the FR3 region and a consensus sequence JH primer. Test for minimal residual disease was conducted by PCR amplification of DNA from remission marrow cells (at day 29 of chemotherapy) with the help of the primer sets used at the time of diagnosis. The amplified DNA was seen by electrophoresis on 6% polyacrylamide gel. Results: A sharp clonal band ranging from 90-200 bp indicated a positive reaction. Of 50 patients, 28 (56%) were positive for Ig gene rearrangement on PCR at the end of induction, 17 (34%) patients were found to be negative for minimal residual disease, 2 (4%) patients died during induction therapy, and 3 (6%) patients did not come for follow-up. Conclusion: Molecular approaches have allowed us to detect low level of residual disease which is not detected by cytomorphological methods. Minimal residual disease (MRD) by PCR used in this study would definitely help in monitoring of MRD in all patients with leukaemia. Keywords: Ig gene rearrangement, ALL, MRD, PCR